Technology Acceptance Model Dan Delone & Mclean Is Success Model, Terhadap Minat Pembelajaran E-Learning System - Priambodo, Ganang Ramadhan; Aulia Fuad Rahman (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to analyze students at Brawijaya University's acceptance of e-learning using TAM (Technology Acceptance Model) and Delone & McLean. There are nine variables used namely self-efficacy, subjective norm, perceived ease of use, perceived usefulness, system quality, information quality, service quality, behavioral intention to use, and actual use with thirteen research hypotheses. There were 161 respondents in this study who were active students of Brawijaya. Data was obtained from the dissemination of questionnaires through Google Forms. Data analysis with Partial Least Square (PLS) method using PLS software. The results of this study are: (1) subjective norm, self-efficacy, and perceived ease of use has a positive effect on intention; (2) Subjective norm have a positive effect on perceived ease of use; (3) subjective norm, self-efficacy, perceived ease of use, system quality, information quality, service quality did not have a positive effect on behavioral intention to use e-learning system; (4) perceived usefulness has a positive effect on behavioral intention to use e-learning system; (5) behavioral intention to use have a positive effect on actual use e-learning system.